2018
DOI: 10.1136/annrheumdis-2017-212916
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon modulator iberdomide induces degradation of the transcription factors Ikaros and Aiolos: immunomodulation in healthy volunteers and relevance to systemic lupus erythematosus

Abstract: ObjectivesIKZF1 and IKZF3 (encoding transcription factors Ikaros and Aiolos) are susceptibility loci for systemic lupus erythematosus (SLE). The pharmacology of iberdomide (CC-220), a cereblon (CRBN) modulator targeting Ikaros and Aiolos, was studied in SLE patient cells and in a phase 1 healthy volunteer study.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 24 publications
(14 reference statements)
2
69
0
Order By: Relevance
“…Given that UBE2G1 inactivation conferred resistance to all CMs tested and also to cereblon-based PROTACs, patient stratification approaches based on UBE2G1 status might be applicable to the development of IMiD drugs and other novel cereblon modulating agents for a variety of human diseases. Lastly, CC-220, a novel CM that targets IKZF1 and IKZF3 for degradation much more effectively than does LEN or POM, retained strong antitumor activity at clinically achievable concentrations ( Schafer et al, 2018 ) in UBE2G1-deficient myeloma cells, suggesting that human patients with resistance to CM drugs owing to diminished UBE2G1 function may be responsive to next-generation CMs that possess higher efficiency and/or potency for degrading the same target protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that UBE2G1 inactivation conferred resistance to all CMs tested and also to cereblon-based PROTACs, patient stratification approaches based on UBE2G1 status might be applicable to the development of IMiD drugs and other novel cereblon modulating agents for a variety of human diseases. Lastly, CC-220, a novel CM that targets IKZF1 and IKZF3 for degradation much more effectively than does LEN or POM, retained strong antitumor activity at clinically achievable concentrations ( Schafer et al, 2018 ) in UBE2G1-deficient myeloma cells, suggesting that human patients with resistance to CM drugs owing to diminished UBE2G1 function may be responsive to next-generation CMs that possess higher efficiency and/or potency for degrading the same target protein.…”
Section: Discussionmentioning
confidence: 99%
“…All three IMiD drugs promote the degradation of two hematopoietic transcription factors IKZF1 and IKZF3 to achieve anti-myeloma activity ( Krönke et al, 2014 ) ( Lu et al, 2014a ) ( Gandhi et al, 2014 ), whereas only LEN targets CK1α for effective degradation ( Krönke et al, 2015 ), which is presumably linked to its efficacy in myelodysplastic syndrome with chromosome 5q deletion. CC-220 is a significantly more potent IKZF1 and IKZF3 degrader than IMiD drugs ( Matyskiela et al, 2018 ) ( Nakayama et al, 2017 ) ( Schafer et al, 2018 ), and it is currently in clinical trials for relapsed/refractory multiple myeloma and systemic lupus erythematosus. By contrast, CC-885 is the only aforementioned cereblon modulating agent that allows cereblon to recognize translation termination factor GSPT1 for ubiquitination and degradation ( Matyskiela et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…THAL, LEN and POM promote the degradation of two hematopoietic transcription factors IKZF1 and IKZF3 to achieve anti-myeloma activity (Kronke et al, 2014) (Lu et al, 2014a) (Gandhi et al, 2014), whereas only LEN targets CK1α for effective degradation (Kronke et al, 2015), which is presumably linked to its efficacy in myelodysplastic syndrome with chromosome 5q deletion. CC-220 is a significantly more potent IKZF1 and IKZF3 degrader than IMiD drugs (Matyskiela et al, 2018) (Nakayama et al, 2017) (Schafer et al, 2018), and it is currently in clinical trials for relapsed/refractory multiple myeloma and systemic lupus erythematosus. By contrast, CC-885 is the only aforementioned cereblon modulating agent that allows cereblon to recognize translation termination factor GSPT1 for ubiquitination and degradation (Matyskiela et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, CC-220 administration causes the degradation of IKZF1 and IKZF3 in B cells, T cells and monocytes. In addition, CC-220 inhibited the production of anti-dsDNA and anti-phospholipid autoantibodies in cultured peripheral blood mononuclear cells (PBMCs) from SLE patients [49]. Thus, this study demonstrated the tolerated safety and pharmacodynamic activity of CC-220, indicating its promising clinical development for SLE.…”
Section: Cc-220 (Iberdomide)mentioning
confidence: 60%
“…Recently, a double-blinded, placebo-controlled, single dose-escalation phase 1 study (NCT01733875) has been carried out in healthy volunteers to evaluate safety, pharmacokinetics and pharmacodynamics of CC-220. In the latest report, 56 healthy volunteers were enrolled and randomized into 7 cohorts [49]. In each cohort, six subjects took a single dose of 0.03 to 6 mg CC-220 and two subjects received placebo orally.…”
Section: Cc-220 (Iberdomide)mentioning
confidence: 99%